Pengaruh Penerapan Model Guided Discovery Learning Berbantuan Canva terhadap Kemampuan Penalaran Matematis Peserta Didik SMA - Ardianti, Zahra Kartika; Arnellis; Fauzan, Ahmad; Khairani (Jurnal PEKA (Pendidikan Matematika), 2026)
Mathematical reasoning ability is an essential competency in mathematics learning, yet Indonesian students generally demonstrate relatively low levels of this ability. This study aimed to examine whether students taught using the Guided Discovery Learning (GDL) model assisted by Canva achieved better mathematical reasoning ability than those taught using direct instruction. A quasi-experimental approach with a nonequivalent posttest-only control group design was employed. The sample consisted of 80 tenth-grade students at SMAN 2 Lubuk Basung, including 40 students in the experimental group and 40 students in the control group, selected through purposive sampling. Data were collected using a mathematical reasoning ability test and analyzed using a one-tailed independent-samples t-test. The experimental group obtained a higher mean score (67.71) than the control group (52.92). The difference was statistically significant (p-value = 0,001 < 0,05), with a medium effect size (Cohen's d = 0.72). These findings indicate that learning through the GDL model assisted by Canva was associated with higher mathematical reasoning ability than learning through direct instruction.